(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aimed to identify the importance of establishing a robot laboratory compatible with the challenges of the 21st century, whether in private or government schools. It also aimed to identify the role of the robot in the educational process and what it provides attractive tools to simplify the understanding of concepts positively and effectively. The study contained a feasibility study to create a laboratory Robot, and the researcher used the methodology of decision analysis through the philosophy of decision-making models (influence charts and decision tree) within the limits of his knowledge and knowledge. The results of the study showed the following: The theoretical framework for the effectiveness of building a robot laboratory at the school was revealed. • Integration of the robot with education using the modern methods of the 21st century, due to the attraction of the love of study by students, especially in the elementary stage. • Contributing to the development of positive and recent trends towards the concept of robot education in education, and changing negative trends if they exist. In light of these results, the researcher recommended the most important recommendations: 1) It is very important to use decision analysis models (decision tree, impact diagrams) for ease of use, dealing with alternatives, and reaching the best possible decision. 2) Decision trees and influence diagrams complement each other, as they work as one spirit to make the right, appropriate, and quality decision. 3) Influencing schemes and decision trees deal with ambiguity and suspicion, and this facilitates the appropriate decision-making process by drawing logical relationships between all elements for foresight